THE ROLE OF WOMEN IN RASTRAKOTA SOCIETY AND POLITICS (International Journal of Food and Nutritional Sciences, 2023)
The role of women in Rastrakuta society and politics, spanning from the 8th to the10th centuries CE, was multifaceted and influential despite the overarching patriarchalconstraints of the time. Women in the Rastrakuta dynasty exerted significant influencethrough strategic marriages, familial connections, religious and cultural patronage, andeconomic activities. Royal women, such as queens and princesses, were pivotal in formingdynastic alliances through marriage, which served as political tools to secure loyalty andpeace among neighboring states. They often acted as advisors and regents, exercisingsubstantial behind-the-scenes political power, and played crucial roles in mediating conflictsand maintaining stability within the royal court.